Carbohydrates, growth and production of -roxo de valinhos- fig tree in initial development under irrigation management - Souza, Manoel Euzébio de; Leonel, Sarita [UNESP]; Silva, Andréa Carvalho da; Souza, Adilson Pacheco de; Martin, Rafaela Lopes [UNESP]; Tanaka, Adriana Aki (Scientific Research Publishing, 2015)
The carbohydrates translocation and consequently growth and production of fig tree (Ficuscarica L.) vary according to the different management on cultivation conditions. The aim of this study was to evaluate the changes in the levels and total carbohydrates accumulation together with growth and “Roxo de Valinhos” fig trees production onimplementation of orchards in initial phase, cultivated with and without irrigation. We adopted a factorial arrangement (2 x 7) with four repetitions distributed in installments (with and without irrigation) subdivided in time (collect time). Destructive analyzes were performed at 40, 80, 120, 160, 200, 240 and 280 days after pruning (DAP) and are measured: stem diameter and branch, stem length and branch, number of leaves, internodes and fruit. Subsequently, the plant parts were sectioned to obtain the leaf area, length and roots volume, fresh and dry matter weight. The number, weight and total productivity of fruits were evaluated. The media of all growth attributes and production characteristics were higher in treatments with water irrigation. The total carbohydrate content was higher at 120 and 160 DAP and the carbohydrates accumulation was increasing for most institutions over the plants development, except for the leaves that showed a decrease in the levels at 160 DAP. The fruits showed greater carbohydrates accumulation in relation to the other evaluated organs.
Keywords: Ficus carica L.; Water management; Growth analysis